PEMBERDAYAAN KELAS GIZI REMAJA CEGAH STUNTING MELALUI PROGRAM DASHAT DAN EMO DEMO DI SMA SWASTA DARUL HIKMAH DESA PAGUTAN KOTA MATARAM - Septiani, Baiq Dewi Sukma; Ardiansyah, Lalu Dwi Satria; Sulistiawati, Febrina (Jurnal Abdi Insani, 2024)
Stunting is a condition of stunted growth and physical development of children, caused by chronic lack of nutritional intake or repeated infections. The impact of stunting not only affects height, but also brain development, intelligence, and productivity of children in the future. Data from the Basic Health Research of West Nusa Tenggara Province shows that the prevalence of adolescent girls aged 16-18 years with very short nutritional status is 2.67% and short nutritional status is 21.79%, while in adolescent boys the very short nutritional status is 4.97% and the short nutritional status category is 70.65% while in Mataram City the prevalence of adolescents aged 16-18 years with very short nutritional status is 0.98% and short nutritional status is 19.99%. The purpose of this activity is to form an adolescent nutrition class to prevent stunting through the Healthy Kitchen to Overcome Stunting (DASHAT) program and Emotional Demonstration through the Snake and Ladder game in an effort to prevent stunting early on. The activity method starts from the Formation of the "Teenager Nutrition Class to Prevent Stunting" Group through the Healthy Kitchen Program to Overcome Stunting (DASHAT) with training in processing local food ingredients into healthy menus for teenagers and the Emotional Demonstration Nutrition Education Program (EMO DEMO) using the Snakes and Ladders stunting game media with 20 members who are representatives of students from Darul Hikmah Private High School, Pagutan Village, Mataram City, classes X-XII who will later become facilitators for other students and teenagers around the school in efforts to prevent stunting early on. Before the activity was carried out, a group discussion forum was held with partners. In addition, in the implementation of the activity, a measurement of the level of knowledge of teenagers about nutrition was also carried out through a pre-post test. The results of the activity showed that there was an increase in the average level of knowledge after being given emotional demonstration nutrition education through the Snakes and Ladders game to prevent stunting (post-test). Through this activity, the Healthy Kitchen to Overcome Stunting (DASHAT) has also been formed which will be routinely carried out at school by the teenager class to prevent stunting with other friends. The conclusion of this activity is the formation of a class group for teenagers to prevent stunting, the formation of a Healthy Kitchen to Overcome Stunting (DASHAT) in schools that routinely carry out cooking class activities and increased understanding of teenagers regarding the importance of nutrition and balanced nutritional intake in efforts to prevent nutritional problems in teenagers.